Variabilidade hidrológica e o fluxo de elementos-traço na bacia do Rio Negro - AM - Vaz, Bruna (Instituto Nacional de Pesquisas da Amazônia - INPA, 2023)
ABSTRACT Hydrological variability and the of the flux concentration of trace elements in the Negro River Basin The variability and dynamics of the flux concentration of dissolved trace elements (V, Ni, Rb, Cd, Ba, Pb, U, Cr, As, Ti, Zr, Sn) in the Negro River Basin was evaluated in: spatial variation of the years 1995 and 1996 and the temporal variation in two stations of the ORE-HYBAM: Caracaraí and Serrinha in the period from 2003 to 2018. These two stations exhibited changes in their fluxes, according to their locations, being in Caracaraí a well-defined seasonal pattern of the elements and higher concentration, however by the flux balance, we observe that in Serrinha, comes the highest concentration flux of the elements. This distinction can be explained by the dilution factor, since the average flow rate at Serrinha (17,019.24 m³.s-¹) is higher than the average flow rate at Caracaraí (3,306.88 m³.s-¹). Elements like Pb, U, Cr, Ti, Sn are controlled by the seasonality of the Negro and Branco rivers, and present a unimodal regime, with high concentrations during flood and low concentrations during the dry period. Elements that present little variation with the flow are V, Ni, Rb and Ba. Cd showed increasing concentration values, associated with increasing flow, with its maximum concentration at flood. Zr presented the maximum peak up to two months after the peak discharge, having maximum concentration in the drought. Among the elements, As is strongly influenced by the dilution of the river at Serrinha, presenting higher concentrations in the drought. In summary, the results obtained in this research allowed us to understand the flux of trace elements in the Negro River basin. Keywords: Trace elements; Negro River Basin; Geochemistry.
Hydrological variability and the of the flux concentration of trace elements in the Negro River Basin
Keywords: Variabilidade hidrológica; Fluxo dos elementos-traço; Bacia do Rio Negro; Geoquímica